2019
DOI: 10.1038/s41598-019-51022-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain lateralization probed by water diffusion at the atomic to micrometric scale

Abstract: Combined neutron scattering and diffusion nuclear magnetic resonance experiments have been used to reveal significant interregional asymmetries (lateralization) in bovine brain hemispheres in terms of myelin arrangement and water dynamics at micron to atomic scales. Thicker myelin sheaths were found in the left hemisphere using neutron diffraction. 4.7 T dMRI and quasi-elastic neutron experiments highlighted significant differences in the properties of water dynamics in the two hemispheres. The results were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…It is known that bacterial cell pellets contain about 70–80% of water and in addition biomolecules . Hence, a model previously developed to analyze QENS data on neurological tissue or on the same prokaryotes having a similar or identical molecular composition was applied: where B ( q ) stands for the background and R ( q , ω ) for the resolution, by which the theoretical model function must be convoluted to account for instrumental broadening. The parameters which could be extracted were the fractions of atoms contributing to elastic scattering ( p el ), bulk ( p bulk ), and hydration water ( p hyd ) and the proteome ( p prot ), with p el + p bulk + p hyd + p prot = 1.…”
Section: Crowding In Living Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that bacterial cell pellets contain about 70–80% of water and in addition biomolecules . Hence, a model previously developed to analyze QENS data on neurological tissue or on the same prokaryotes having a similar or identical molecular composition was applied: where B ( q ) stands for the background and R ( q , ω ) for the resolution, by which the theoretical model function must be convoluted to account for instrumental broadening. The parameters which could be extracted were the fractions of atoms contributing to elastic scattering ( p el ), bulk ( p bulk ), and hydration water ( p hyd ) and the proteome ( p prot ), with p el + p bulk + p hyd + p prot = 1.…”
Section: Crowding In Living Cellsmentioning
confidence: 99%
“…It is known that bacterial cell pellets contain about 70− 80% of water and in addition biomolecules. 140 Hence, a model previously developed to analyze QENS data on neurological tissue 141 or on the same prokaryotes 130 having a similar or identical molecular composition was applied:…”
Section: Biological Cells and Lysed Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the very beginning until the current days, many experiments have been performed with rather simple organisms, such as bacteria, which are valuable models to show that incoherent neutron scattering can provide useful (and interpretable) information on water dynamics within living systems [ 40 , 41 , 42 , 43 ]. The limits of the technique were gradually extended and, to this date, QENS allowed for investigating quite complex systems, including mammalian cells (including humans) and even multicellular organisms [ 44 , 45 , 46 , 47 , 48 ]. In all these cases, the very complex cellular environment poses a major challenge to describing the behavior and roles played by water.…”
Section: Qens and Cancer Cellsmentioning
confidence: 99%
“…[1][2][3][4] Healthy individuals are typically thought to rely on left hemispheric activity for comprehension and generation of meaningful language, specifically for processing syntactic and lexical semantic information. [5][6][7][8][9] Functional magnetic resonance imaging (fMRI) studies have shown dominant left hemispheric responses and right hemispheric suppression during such language tasks in full tem (FT) born infants and adults. 10,11 VPT children, on the other hand, were shown to have both hemispheres involved during language tasks until the age of 11-12 years.…”
Section: Introductionmentioning
confidence: 99%